Indução à maturação final, ovulação e fertilização do cachara, Pseudoplatystoma fasciatum, em cativeiro - Leonardo, Antonio Fernando Gervásio [UNESP] (2003)
In the months of January 2001 and January 2002, females of cachara, Pseudoplatystoma fasciatum, were selected during their first and second gonadal maturation (2 years and 7 months old and 3 years and seven months old, respectively) according to the association between the external anatomic characteristics and internal, showing distribution of oocyte diameter frequency with a single mode of 937.5 mm; 82.5 % of central nuclei and 17.5 % of eccentric nuclei. Histologically, it was observed that the majority of oocytes were in final maturation. Nine females in first maturation received 2 doses of carp pituitary extract (CPE), 0.5 mg/kg and 5.0 mg/kg (T1); seven received 2 doses of hCG, 5 and 10 IU/g (T2); five received doses of carp pituitary extract 0.5 mg/kg and hCG 5IU/g (T3); four received 0.9 % saline (T4). Nine females from T1 and seven from T2 presented oocytes with the same diameter at the moment of oocyte release; 100 % with germinal vesicle breakdown and fertilization rate of 53.44 + 18.3 and 54.81 + 11.8 %; larvae number of 165,330 + 94.1 and 158,570 + 20.6, respectively. The five females from T3 didn't respond to the hormonal treatment. The four females from T4 belonged to the control group. In January 2002, 6 of the 15 selected females that were going through the second cycle received T1; 5 received T2; and 4 received T4, showing oocyte diameters similar to the ones in the first maturation. On the third samples, the females from T1 showed mode shift to the right and modal diameter of 1062.5mm; the females from T2 presented diameters ranging from 937.5mm to 1125.0mm; fertilization rates of 56.08 + 30.9 and 81.90 + 17.3 %; 364,547 + 244 and 633,129 + 190 larvae, respectively. Under light microscopy, it was noticed that the oocytes were similar to the ones at the previous stage. A better efficiency of T2 was verified on the second maturation females, considering the fertilization rates ...